New Advances in Melanoma - Larribère, Lionel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Melanoma is a very aggressive tumor which is derived from the transformation of pigment-producing cells termed the melanocytes. This cancer type accounts for most of the deaths associated with skin cancer as well as its incidence and is in constant evolution. Because of the rapid and very high metastatic potential of this tumor, melanoma prognosis has been quite poor for a long time. In the past decade, groundbreaking discoveries in the melanoma research field have led to the development of two main treatment strategies: combination therapies targeting specific kinases or combination therapies focused on immune checkpoint inhibitors (ICIs). These treatment approaches have become the standard of care in most cancer centers and significantly improved the prognosis and overall survival of advanced melanoma patients. Nevertheless, many patients do not benefit from or even respond to these treatments. It is therefore essential to better comprehend the phenomenon of drug resistance, immune escape mechanisms, as well as to search for alternative treatment strategies. In addition, strong predictive biomarkers are desperately needed to improve clinical efficacy. The aim of this Special Issue is to present recent advances in the field of melanoma research, in which the abovementioned areas represent the primary focus, and other relevant themes are also discussed.